Study of growth and yield in different media for chilli / Muhammad Adi Azfar Anwar - Anwar, Muhammad Adi Azfar (2019)
Chilli (Capsicum annum) is widely cultivated in Malaysia. However, selection of medium will affect rate of growth performance, yield and costing. In this study, three different medium was used; 100% cocopeat, 100% burnt rice husk and mixture (50% cocopeat with 50% burnt rice husk). The aim was used to investigate the growth performance and yield of chilli on different medium and to determine the best medium for chilli fertigation. This experiment was conducted at Share Farm, UiTM Jasin Campus, Melaka and 15 seeds of Sakata 461 F1 Hybrids variety were used. The experiment was conducted in a Complete Randomized Design (CRD) with five replications and three treatments. Each experimental unit consisted of 15 polybags, which made up a total of five plants per treatment. The plots were triangle spaced at three feet between treatments and the distance between plants of the same treatment was 1.5 feet. The medium were filled into polybag size 16 x 16. The data were collected and recorded every week for every stage (vegetative stage, flowering stage and fruiting stage). The parameter were plant height, number of leaves, number of fruits and weight of fruit per plant of the crops were measured and recorded to see the effect of the treatments towards the chilli. Based on the study, it was found that the number of leaves has significant value which was 0.00 at the flowering stage and 0.23 at the fruiting stage. The best medium at the flowering stage for number of leaves was T1 with 23 leaves and T3 with 200 leaves at the fruiting stage. The plant height value has significant value which was 0.00 at the vegetative stage, 0.02 at the flowering stage and 0.00 at the fruiting stage. The best medium at the vegetative stage for plant height is T1 22.00cm, T1 37.00cm at the flowering stage and T1 (62.4cm) at the fruiting stage. However, there was a no significant difference between the treatments (P>0.05) for number of fruits and weight of fruit. It is because medium material such as cocopeat and burnt rice husk that naturally possesses a 5-6 pH range, it will provide a relatively optimal availability of nutrients with minimal intervention to help in yield performance. As conclusion, cocopeat has higher impact on the growth and yield performance.